Peran Kepemimpinan Kristen Berkarakter Kristus bagi Pertumbuhan Gereja - Dau, Mersi Prastika; Benu, Yance Novrianti (STTI Harvest Semarang, 2024)
Christian leadership with the character of Christ has a very important role in church growth. Christian leaders who have the character of Christ are also able to mobilize God's people to actively participate in church services. This study uses a literature study approach, by examining references as a basis for research conducted from relevant sources according to the topic of discussion. The data collection process begins with selecting a reference source, then analyzing the data and providing a descriptive explanation of the results obtained. The results of this research found that the context of church growth is closely related to Christian leadership with the character of Christ. The character of Christ is the main key to effective Christian leadership and has a positive impact on church growth. It can be underlined that Christian leadership with the character of Christ can help the church grow and achieve spiritual goals. Leadership based on the character of Christ is a solid foundation for the growth and success of the Christian church. AbstrakKepemimpinan Kristen yang berkarakter Kristus memiliki peranan yang sangat penting dalam pertumbuhan gereja. Pemimpin Kristen yang berkarakter Kristus juga mampu mengerahkan umat Tuhan untuk berpartisipasi aktif dalam pelayanan gereja. Kajian ini menggunakan pendekatan studi kepustakaan, dengan menelaah referensi-referensi sebagai tumpuan bagi riset yang dilakukan dari sumber-sumber yang relevan sesuai dengan topik pembahasan. Proses pengumpulan data dimulai dengan memilih sumber referensi, lalu kemudian menganalisis data dan memberikan penjelasan deskriptif mengenai hasil yang diperoleh. Hasil penelitian ini menemukan bahwa konteks pertumbuhan gereja erat kaitannya dengan kepemimpinan Kristen yang berkarakter Kristus. Karakter Kristus adalah kunci utama dalam kepemimpinan Kristen yang efektif dan berdampak positif terhadap pertumbuhan gereja. Dapat digarisbawahi, kepemimpinan Kristen yang berkarakter Kristus dapat membantu gereja bertumbuh dan mencapai tujuan rohani. Kepemimpinan yang didasarkan pada karakter Kristus adalah landasan yang kokoh untuk pertumbuhan dan keberhasilan gereja Kristen.